Tracking the Health Resources in Ukraine - World Bank Group (World Bank, Washington, DC, 2018)
While Ukraine has spent a significant amount of resources on health, its health outcomes fare poorly when compared with other European countries. For example, average life expectancy at birth in Ukraine has improved from the lowest, 66.8 years in 1995 to 71.4 years in 2016, but is still nine years behind the EU average of 80.6 years. The country has much higher death rates related to noncommunicable diseases (NCD) than the neighboring countries on their west. The suboptimal health outcomes point to the inefficient use of public resources, which is magnified by the shortage of funds during the recent economic crisis and conflicts. However, although the Public Finance Review (PFR)has been conducted recently to assess the allocation and effectiveness of public spending,there is no study to track the resource flows in order to identify the magnitude of theinefficiency and waste in the health sector.